ANXIETY OF MICHAEL REFLECTED IN THE LAST KISS MOVIEDIRECTED BY TONY GOLDWYN: A PSYCHOANALYTIC APPROACH. - DARYATI, DWI (2010)
The problem statement of this study is how Michael's anxiety influences his personality in Tony Goldwyn's The Last Kiss. The object of the research is the movie entitled The Last Kiss, directed by Tony Goldwyn published in 2006. The researcher uses Sigmund Freud's psychoanalytic theory. The study belongs to qualitative study in which the writer uses two data sources, namely primary data source and secondary data source. The primary data source is The Last Kiss movie itself and the secondary data source is the other sources related to the analysis such as the author biography, books of literary theory and also psychological books, particularly related to the psychoanalytic theory of Sigmund Freud. The method of data collection is library research. The technique of data analysis is descriptive analysis. From the result of analysis, it can be drawn some conclusion. Firstly, the elements of the movie present a good unity. It consists of exposition, complication, climax, and resolution. Secondly, the anxiety of Michael influences his Id to do something under his unconscious. As the work of Ego, Michael fulfills the Id demand. Nevertheless, his Superego can differentiate what is true and false.